ADAPTIVE EDTECH PLATFORMS FOR TRAINING TEACHERS IN IT MICRO-QUALIFICATIONS: A REVIEW OF INTERNATIONAL AND KAZAKHSTANI EXPERIENCE - Mussirat, Ерзат; Bidaibekov, Есен; Pak, Николай; Oshanova, Нуржамал; Salgoja, Индира (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2026)
This article reviews the Kazakh and international experience of adaptive EdTech platforms for training teachers in IT micro-skills. In accordance with the objectives of the study, the pedagogical potential of digital platforms aimed at forming IT micro-skills in the context of continuous professional development of teachers is analyzed, and the theoretical foundations of their design and use are systematized. The following methods were used in the study: comparative analysis, content analysis and systematization. The article considers the functional capabilities, adaptability elements and design for teachers of international (Coursera, edX, Microsoft Learn, etc.) and Kazakhstani EdTech platforms. The results show that adaptive learning mechanisms play an important role in the formation of teachers along an individual learning trajectory and the development of IT micro-skills. The results of the study allow us to identify the scientific and methodological foundations of designing adaptive EdTech platforms for teachers.